PENGUATAN TATA KELOLA AKUNTANSI PUBLIK MELALUI KOMUNIKASI EFEKTIF DAN KEPEMIMPINAN DIGITAL DI KPID KALIMANTAN TIMUR - Yudea, Yudea; Sofyaun, Ashari; Hernadi Moorcy, Nadi (Fakultas Ekonomi Universitas Balikpapan, 2025)
This study aims to analyze the strengthening of public accounting governance through effective communication and digital leadership at the Regional Indonesian Broadcasting Commission (RIBC) of East Kalimantan Province. Amidst increasing demands for transparency and accountability in the public sector, the implementation of effective communication strategies and the adoption of digital leadership are crucial. The research method involved a socialization and discussion event held on October 2, 2025, from 13:00 to 16:00 Wita, at the Aston Hotel Samarinda. This activity was attended by 37 staff members of RBIC East Kalimantan Province and by Yudea (Keynote Speaker), an Accounting Lecturer from the Faculty of Economics and Business, University of Balikpapan. The findings are expected to provide a comprehensive understanding of the best strategies to enhance RBIC East Kalimantan's Province public accounting governance in the digital era, focusing on improving efficiency, accountability, and public services through leveraging technology and transparent communication.